Accuracy of diagnostic codes for Dengue Hemorrhagic Fever patients based on anamnesis and supporting examinations in 10 Central Java Hospitals - Sugiyanto, Zaenal; Insyira, Yashinta Chindy; Ernawati, Eni; Novendriani, Putri; Fhadil, Faizal; Nurul, Siti Hana; Shifa, Aura; Sarmaeda, Amara; Galih, M. Ridho; Salim, Fajar Sabila; Agung, Devika (Procedia of Engineering and Life Science, 2024)
Dengue Hemorrhagic Fever (DHF) often occurs every year and attacks all age groups and is related to community habits and environmental factors. However, there are incomplete forms and some codes that are not yet appropriate. This study aims to determine the accuracy of the Dengue Hemorrhagic Fever disease code in 9 hospitals in Central Java. This study is descriptive with a case study approach. The data collection method uses an observation sheet to observe 1653 Medical Record Documents. The results showed that Dengue Fever patients The main complaint in DHF patients was fever 1653 (100%) and other complaints such as: vomiting, shock, heartburn, nosebleeds and petechia. Most patients experienced a decrease in platelets <150.00 1448 (87.6%), a decrease in leukocytes <5000 there were 254 (15.4%). Most with the main diagnosis were DHF 1526 (92.3%). most of the primary diagnosis codes are A91 there are 1526 (92.3) medical record documents. Accurate codes are 1529 (92.5%), while inaccurate data are 124 (7.5%).. Suggestions in this study, Hospitals should complete all patient information and physical examination results or supporting, especially the number of platelets that affect the decision on diagnosis and primary codes.